Cardiac Dysfunction in a Mouse Vascular Dementia Model of Bilateral Common Carotid Artery Stenosis - An, Lulu; Chopp, Michael; Zacharek, Alex; Shen, Yi; Chen, Zhili; Qian, Yu; Li, Wei; Landschoot-Ward, Julie; Liu, Zhongwu; Venkat, Poornima (Frontiers in Cardiovascular Medicine, 2021)
Background: Cardiac function is associated with cognitive function. Previously, we found that stroke and traumatic brain injury evoke cardiac dysfunction in mice. In this study, we investigate whether bilateral common carotid artery stenosis (BCAS), a model that induces vascular dementia (VaD) in mice, induces cardiac dysfunction. Methods: Late-adult (6–8 months) C57BL/6J mice were subjected to sham surgery (n = 6) or BCAS (n = 8). BCAS was performed by applying microcoils (0.16 mm internal diameter) around both common carotid arteries. Cerebral blood flow and cognitive function tests were performed 21–28 days post-BCAS. Echocardiography was conducted in conscious mice 29 days after BCAS. Mice were sacrificed 30 days after BCAS. Heart tissues were isolated for immunohistochemical evaluation and real-time PCR assay. Results: Compared to sham mice, BCAS in mice significantly induced cerebral hypoperfusion and cognitive dysfunction, increased cardiac hypertrophy, as indicated by the increased heart weight and the ratio of heart weight/body weight, and induced cardiac dysfunction and left ventricular (LV) enlargement, indicated by a decreased LV ejection fraction (LVEF) and LV fractional shortening (LVFS), increased LV dimension (LVD), and increased LV mass. Cognitive deficits significantly correlated with cardiac deficits. BCAS mice also exhibited significantly increased cardiac fibrosis, increased oxidative stress, as indicated by 4-hydroxynonenal and NADPH oxidase-2, increased leukocyte and macrophage infiltration into the heart, and increased cardiac interleukin-6 and thrombin gene expression. Conclusions: BCAS in mice without primary cardiac disease provokes cardiac dysfunction, which, in part, may be mediated by increased inflammation and oxidative stress.